IMPLEMENTASI LAYANAN KONSELING INDIVIDUAL BERBASIS ASESMEN KEBUTUHAN UNTUK MENGEMBANGANKAN KEPERCAYAAN DIRI ANAK PANTI ASUHAN - Audina Tri Gustari; Arga Satrio Prabowo; Meilla Dwi Nurmala (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of individual counseling services based on a needs assessment to develop the self-confidence of a child at the Toriqul Jannah Orphanage. This research was motivated by the discovery of an orphanage resident who had low self-confidence based on the initial assessment using the Alat Ungkap Masalah (AUM). The intervention was carried out using individual counseling focused on managing anxiety, strengthening self-confidence, and self-adjustment. The results showed a significant improvement in the subject's self-confidence. In the first session, the evaluation score was 8 (Fair category), which increased to 13 (Good category) in the second session, and reached a maximum score of 15 (Good/Excellent category) in the final session. The conclusion of this study indicates that AUM-based individual counseling is highly effective as an intensive assistance approach in overcoming personal problems and increasing the self-confidence of orphanage children.